Interpretación de las relaciones intragrupales de riesgos y de lesiones mediante análisis cluster jerárquico - Conte Solano, Juan Carlos (2008)
From the analyses cluster of risks and of injuries, there is obtained the sequence of the process of conglomeration, based on this case in Ward’s method. The interest of the above mentioned process of conglomeration, for the case of the variables risk and injury, components of the accident at work, centres that allows interpreting the relations between the above mentioned variables stepwise, that is to say, it allows interpreting the existing affinities between the above mentioned variables to scale intragroup. Hereby can be explained the relations that the diverse clusters are describing. For the case of the accidents at work this interpretive information performs vital importance on having made possible to associate a meaning with the relations between variables obtained mathematically, conceptual base of any intelligent system.